IMPROVING UNDERSTANDING OF REPRODUCTIVE HEALTH IN SELF-PROTECTION USING MEDIA CROSSWORD PUZZLE MAGNETIC BOARDS IN STUDENTS WITH INTELLECTUAL DISABILITIES - Joleatin; Efi Kristiana (Universitas STRADA Indonesia, 2023)
Background: Adolescent reproductive health is an important indicator in achieving public health development (Notoatmodjo, 2011). Method: The statistical test used was the Paired Sample T-Test, in which the subject was measured twice on 28 students with intellectual disabilities before and after being given the material. Results : The score before being given reproductive health material in self-protection, obtained the lowest score of 14.3 and the highest score of 100 with an average score of 49.5. Analysis: The results of the analysis show that the Sig.(2-tailed) value is 0.000, with an α of 0.05, it means that there is a significant difference in the average increase in the score for understanding reproductive health in self-protection. Conclusion: Magnetic board crossword puzzle media was effective in providing an understanding of health education to students with intellectual disabilities, especially on reproductive health material in self-protection.